Oculovagal reflex in paediatric orbital floor fractures mimicking head injury. Issue 5 (22nd April 2009) - Cobb, A; Murthy, R; Manisali, M; Uddin, J; Toma, A
Abstract : Background: The oculovagal reflex is well described in ophthalmic surgery, but may be caused by any manner of pressure on the globe. Children with orbital blowout fractures present in a different manner from adults. The classic presentation in children is a white eye injury (ie, no subconjunctival haemorrhage) with upgaze diplopia and general malaise. Methods: A retrospective audit is presented of paediatric and young adult patients referred to the Orbital Service at St George's Hospital who required surgical intervention. Results: One-third of children with orbital blowout fractures are admitted for head injury observations, while the true cause for the symptoms goes unrecognised and uninvestigated. Conclusions: Orbital blowout fractures in children require more swift intervention than in adults if muscle ischaemia and permanent impairment of the vision is to be avoided. The delay for head injury observation may therefore compromise the surgical outcome.